1971
DOI: 10.1128/iai.3.5.688-693.1971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol on the Clearance of Airborne Pneumococci and the Rate of Pneumococcal Transformations in the Lung

Abstract: The rate of clearance of pneumococci from the lungs of mice infected by aerosols was found to vary inversely with the virulence of the pneumococci. Treatment of of the mice with ethanol delayed the clearance and increased the rate of pneumococcal transformations in vivo. The transfer of genetic information from one Pneumococcus to another by transformation with freshly released deoxyribonucleic acid is known to occur both in vitro (1, 10, 16) and in vivo (4, 8, 18, 19). Conant and Sawyer (4) have recently repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…In these studies, chronic ethanol ingestion increased GBS colonization of lung tissue and decreased bacterial clearance from the alveolar space when compared with the control group. These results were similar to that observed for clearance of Streptococcus pneumoniae (Auerbach‐Rubin and Ottolenghi‐Nightingale, 1971; Boé et al., 2001) after acute ethanol intoxication. Therefore, chronic ethanol ingestion increased the risk of GBS infection even though this Gram‐positive micro‐organism was less pathogenic than Streptococcus pneumoniae .…”
Section: Discussionsupporting
confidence: 89%
“…In these studies, chronic ethanol ingestion increased GBS colonization of lung tissue and decreased bacterial clearance from the alveolar space when compared with the control group. These results were similar to that observed for clearance of Streptococcus pneumoniae (Auerbach‐Rubin and Ottolenghi‐Nightingale, 1971; Boé et al., 2001) after acute ethanol intoxication. Therefore, chronic ethanol ingestion increased the risk of GBS infection even though this Gram‐positive micro‐organism was less pathogenic than Streptococcus pneumoniae .…”
Section: Discussionsupporting
confidence: 89%
“…The latter laboratory extended these observations to demonstrate that in addition to bacterial genera differences, strain differences existed in the intrapulmonary killing pattern of P. aeruginosa in mice (32). The exceedingly rapid rate of intrapulmonary killing of S. pneumoniae and S. aureus during the initial hours after aerosol challenge has been confirmed by a number of laboratories (1,22,25).…”
Section: Resultsmentioning
confidence: 87%
“…Both acute and chronic ethanol exposure have been shown to affect the phagocytic potential and the ability of these professional antigen presenting cells to express antigen and co-stimulatory molecules on their surface (Table 1). Studies from as early as the 1960's and 70's have shown immunomodulatory effects of ethanol on bacterial clearance (Auerbach-Rubin and Ottolenghi-Nightingale, 1971;Laurenzi et al, 1963). Recent studies have begun to reveal a more in-depth understanding of ethanol's effects on phagocytosis.…”
Section: Ethanol and Phagocytosismentioning
confidence: 99%